2023
DOI: 10.1007/s11739-022-03188-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mobile health-technology integrated care based on the ‘Atrial fibrillation Better Care’ (ABC) pathway in relation to sex: a report from the mAFA-II randomized clinical trial

Abstract: The Mobile Health Technology for Improved Screening and Optimized Integrated Care in AF (mAFA-II) cluster-randomized trial showed that a mobile health (mHealth)-implemented ‘Atrial fibrillation Better Care’ (ABC) pathway approach reduced the risk of adverse events in atrial fibrillation (AF) patients. Whether this benefit can be applied to both males and females is unclear, especially given the suboptimal management and poorer cardiovascular outcomes in females with AF. In this post-hoc analysis, we performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“… 57 China RCT 833 (IC) 1057(UC) 72 ± 12 73 ± 13 33% 42% ≥12 months Death/ischemic stroke/systemic thromboembolism, rehospitalization (IC vs UC): HR, 0.37; 95% CI, 0.26–0.53 Rehospitalizations alone: HR 0.42; 95% CI 0.27–0.64 Stroke/thromboembolism alone: HR 0.17; 95% CI 0.05–0.51 MI/HF/uncontrolled BP: HR 0.29; 95% CI 0.19–0.45 Guo et al. 58 China RCT 2062 (men) 1262 (women) 68 ± 14 70 ± 13 0% 100% ≥12 months Death/ischemic stroke/systemic thromboembolism/rehospitalization (IC vs UC): HR 0.30, 95% CI 0.17–0.52 (men), HR 0.50, 95% CI 0.27–0.92 (women) Thromboembolism: NS Death: HR 0.32, 95% CI 0.12–0.87 (men) Rehospitalization: HR 0.29, 95% CI 0.15–0.57 (men), HR 0.31, 95% CI 0.14–0.68 (women) Bleeding): NS RAF/HF/MI: HR 0.32, 95% CI 0.18–0.56 (men) Luo et al. 59 China Cost benefit analysis NA NA NA 30 y Costs (IC vs UC): US $35,691 vs US $34,601 QALY gain: 7.2749 vs 7.2019 ICER below WTP: US $14,936 vs US $33,438 per QALY Guo et al.…”
Section: Integrated Digital Atrial Fibrillation Management: a Systema...mentioning
confidence: 99%
See 2 more Smart Citations
“… 57 China RCT 833 (IC) 1057(UC) 72 ± 12 73 ± 13 33% 42% ≥12 months Death/ischemic stroke/systemic thromboembolism, rehospitalization (IC vs UC): HR, 0.37; 95% CI, 0.26–0.53 Rehospitalizations alone: HR 0.42; 95% CI 0.27–0.64 Stroke/thromboembolism alone: HR 0.17; 95% CI 0.05–0.51 MI/HF/uncontrolled BP: HR 0.29; 95% CI 0.19–0.45 Guo et al. 58 China RCT 2062 (men) 1262 (women) 68 ± 14 70 ± 13 0% 100% ≥12 months Death/ischemic stroke/systemic thromboembolism/rehospitalization (IC vs UC): HR 0.30, 95% CI 0.17–0.52 (men), HR 0.50, 95% CI 0.27–0.92 (women) Thromboembolism: NS Death: HR 0.32, 95% CI 0.12–0.87 (men) Rehospitalization: HR 0.29, 95% CI 0.15–0.57 (men), HR 0.31, 95% CI 0.14–0.68 (women) Bleeding): NS RAF/HF/MI: HR 0.32, 95% CI 0.18–0.56 (men) Luo et al. 59 China Cost benefit analysis NA NA NA 30 y Costs (IC vs UC): US $35,691 vs US $34,601 QALY gain: 7.2749 vs 7.2019 ICER below WTP: US $14,936 vs US $33,438 per QALY Guo et al.…”
Section: Integrated Digital Atrial Fibrillation Management: a Systema...mentioning
confidence: 99%
“…This superior effect held true for patients with multimorbidity 57 and both in males and females. 58 In a hypothetical cohort within the mAFA-II trial, the base-case analysis indicated cost-effectiveness of applying mHealth-based integrated care for AF with cost-effective ratio of US $14,936 per quality-adjusted life years, which was below the willingness-to-pay (US $33,438 per quality-adjusted life years). 59 However, these findings should be interpreted cautiously due to the model-based approach, short follow-up, region-specific factors, and multiple cost inputs (including expert opinions).…”
Section: Integrated Digital Atrial Fibrillation Management: a Systema...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, further critical issues make the situation more serious, such as the rising aging population, the shortage of health personnel, increasing healthcare costs, and the lack of congruence between investment needs and financing strategies [ 4 , 5 ]. In the last two decades and, more importantly, during and after the COVID-19 emergency, technology has increasingly been used as an instrument to face these challenges [ 5 , 6 , 7 , 8 , 9 , 10 ], thanks to its potential to expand the physical boundaries of healthcare systems, introducing the possibility to offer healthcare services remotely [ 4 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we read with great interest the paper of Guo Y et al [ 3 ], a secondary analysis of the mAFA-II (Mobile Health Technology for Improved Screening and Optimized Integrated Care in AF) trial aimed at exploring whether the effectiveness of mobile-Health implemented ABC intervention varies by patient’s biological sex. While a significant risk reduction of 1-year adverse events (i.e., stroke, thromboembolism, all-cause death, and rehospitalization) was evident in patients allocated to mAFA intervention regardless of sex; yet the sex-by-intervention interaction analysis unrevealed differences in terms of the occurrence of all-cause death and bleeding events.…”
mentioning
confidence: 99%